2015
DOI: 10.1002/smr.1707
|View full text |Cite
|
Sign up to set email alerts
|

A parallel and efficient approach to large scale clone detection

Abstract: We propose a new token-based approach for large -scale code clone detection, which is based on a filtering heuristic that reduces the number of token comparisons when the two code blocks are compared. We also present a MapReduce based parallel algorithm that uses the filtering heuristic and scales to thousands of projects. The filtering heuristic is generic and can also be used in conjunction with other token-based approaches. In that context, we demonstrate how it can increase the retrieval speed and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Sajnani et al [21] implemented a MapReduce based parallel algorithm for code clone detection that is capable of scaling to thousands of projects. Geronimo et al [22] proposed a parallel genetic algorithm that uses MapReduce to automatically generate JUnit test suites.…”
Section: B Related Workmentioning
confidence: 99%
“…Sajnani et al [21] implemented a MapReduce based parallel algorithm for code clone detection that is capable of scaling to thousands of projects. Geronimo et al [22] proposed a parallel genetic algorithm that uses MapReduce to automatically generate JUnit test suites.…”
Section: B Related Workmentioning
confidence: 99%
“…They can be classified into two categories, fine-grained detection [17,23,27,39,41] and unit-level detection [19,35,40].…”
Section: Identifying Code Reuse Between Different Projectsmentioning
confidence: 99%
“…6,[23][24][25][26] Detecting code clones in big code bases have been very useful to overcome security flaws. 14,[27][28][29] Prior research has also shown that there are many fake applications in android…”
Section: Vulnerabilities Discovered In Htc-kernel and Findx-81-kernelmentioning
confidence: 99%
“…https://www.kernel.org/28 https://github.com/CyanogenMod/android_kernel_htc_msm8974 29 https://github.com/znd15/vul_in_HTC_kernel…”
mentioning
confidence: 99%